Lord of California : a novel - Valencia, Andrew (Ig Publishing, 2018)
Set in a future where the United States has dissolved and California is its own independent republic, Lord of California follows the struggles of the Temple family as they work at running a farm on a nationalized land parcel in the central San Joaquin Valley. When the family patriarch, Elliot, dies, it's revealed that he had been keeping five separate families, and in the aftermath of this discovery, his widows and children must come together to keep from losing everything. But their livelihood is threatened when Elliot's estranged son tries to blackmail them, unleashing a series of violent confrontations betwwen different factions of the family.